Impact of cocoa on the human health - Całkosiński, Aleksander; Kostrzewska, Paulina; Majewski, Maciej; Mandera, Amanda; Pawlikowska, Anna; Szuster, Ewa Magdalena (Journal of Education, Health and Sport, 2019)
Humans have consumed foods made from beans from the Theobroma cacao tree for centuries. Already Aztec warriors supported the cocoa powder drink before the battle. In modern society, chocolate has been known for its good taste. Earlier, chocolate used to be criticized for its fat content and its consumption was a sin rather than a remedy, associated with acne, caries, obesity, high blood pressure, coronary artery disease and diabetes. However, the recent discovery of biologically active phenolic compounds in cocoa has changed this perception[14]. Flavonoids, including catechin, epicatechin, and procyanidins predominate in antioxidant activity. Nowadays, in many studies discuss the recent progresses on potential health benefits of cocoa, with a focus on the areas that have been paid little attention so far, such as the role of cocoa in immune regulation, inflammation, neuroprotection, oxidative stress, obesity, and diabetes control[12].The purpose of this review is to interpret research done in the last decade on the benefits of chocolate consumption.